PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH - Putra, 08.05.51.0146 Dadang Febriyanto; Subagyo, Herry (Students Journal of Economic and Management, 2012)
This research aims to find out whether the variable quality of service consisting of tangible, reliability, responsiveness, assurance and emphaty on customer satisfaction. The population in this study is the branch of Micro Laju PT Bank CIMB Niaga in Winong Pati. The selection of the sample (respondents) using simple random sampling technique, because the acquisition is done at random with out regard to existing strata with in the population, such as job title, occupation, age, gender, and othersThe collected data were analyzed using factor analysis to test the validity of question items, Cronbach Alpha formula for Reliability of consumer testing, regression analysis, to test the magnitude of the effect of independent variables were tested by t test to test and prove the partial effect of respective variable free. From the regression equation above, shows that intangible variables is the most dominant factor which has a positive effect in influencing satisfaction nasabah. Nilai large concern of regression coefficient then follow the variable reliability, the variable responsiveness , and variable insurance.Key words: quality of service (tangible, reliability, responsiveness, assurance, emphaty), customer satisfaction.